Experiences Relating to Sexual Well-Being Among Muslim Gynecological Cancer Survivors: A Systematic Review of Qualitative Studies - Samaneh Alinejad Mofrad; Heidi Green; Shailendra Sawleshwarkar; Ibrahim Alananzeh; Ritin Fernandez (Mary Ann Liebert, 2024)
Background: Gynecological cancers are one of the most important threats to women's health worldwide. The objective of this review is to synthesize and present the best available evidence on the experiences relating to sexual well-being among Muslim women with gynecological cancer. Methods: The databases searched included Web of Science, Scopus, SID, Google Scholar, ProQuest, MEDLINE, and CINAHL from the inception of the database until August 2021. The review was guided by the JBI methodology used for qualitative systematic reviews. Findings were collated using the meta-aggregation method through JBI SUMARI. Results: Eight studies involving Muslim women cancer survivors were included in the review. Meta-synthesis of the eight included studies generated 59 findings, which were organized into 14 categories and combined into four synthesized findings. Conclusions: Gynecological cancer and its treatment results in numerous challenges with sexual well-being among Muslim women cancer survivors. Providing information about sexual activity following gynecological cancer, better communication from health care professionals, and support from the husband is essential to overcome the struggle with intimacy and femininity experienced by the women, thus improving the sexual quality of life of Muslim gynecological cancer survivors.